Prediction of anticancer activity of Aliphatic Nitrosoureas using Quantum Chemical QSAR methods - Noorbatcha, Ibrahim Ali; Hamzah, F.; Mohd. Salleh, Hamzah; Syed Osman Idid, Syed Zahir Idid (2011)
Design and development of new anticancer drugs with low toxicity is a very challenging task and computer aided methods are being increasingly used to solve this problem. In this research we investigate the anticancer activity of aliphatic nitrosoureas using quantum chemical quantitative structure activity relation (qcQAR) approach. In this method the physic-chemical properties, known as descriptors, necessary for predicting quantitative structure activity relations is obtained from semi empirical quantum chemical methods. We have used Recife Model 1 (RM1) to optimize the structure of the molecules and to calculate the quantum chemical descriptors, while heuristic and best multilinear regression methodswere applied to obtain the best correlation. Two data sets containing aliphatic nitrosoureas and chloroethyl substituted nitrosoureas, are used in the present calculations. The best QSAR equations obtained here can be used to design new anticancer drugs prior to resorting to experimental activity studies.